Model for Municipal Solid Waste Management of Koh Samui District, Surattani Province - Chaiji, Jureerat (JOURNAL OF SOUTHERN TECHNOLOGY, 2021)
This article is a part of study on how to solve the problem of Municipal solid waste of Koh Samui District, Surat Thani province. The objective is to totally get rid of existing Municipal solid waste and to reduce increasing garbage disposal in the future, with effective cost and benefit to the community as a whole minimizing the environment impacts. This study shows that at present (April 2012) the problem of Municipal solid waste in Koh Samui has become intense due to the malfunctioning of the 2 existing incinerator, that were used to eliminate garbage of about 15,000 tons and this return increase the quantity of garbage 168 ton per day. Nowadays, burying of garbage which is not good management affected the soil and underground water in neighborhood including poor drainage leachate in the Maret canal has impacted on well-being in the community. An approach of effectively getting rid of garbage is by separating the garbage that comes from the origin. This is done by burying the separated waste garbage to reduce biogas and garbage that cannot be recycled will be separated to produce RDF. For maximum benefit, the suggestion should be the power plant contraction which RDF together with biogas from the garbage as mentioned above. Estimating the quantity of increasing garbage of 168 tons when recycled can generate electricity of about 1.5 megawatts. However, in order to support it future expansion power plant construction of 3.0 megawatts in singe are being interlude the amount of using low cost power plant construction is about 310 Million Baht. However, evaluating income according to fundamental economic by selling electricity to the Regional